2019
DOI: 10.2147/dddt.s170969
|View full text |Cite
|
Sign up to set email alerts
|

<p>Spotlight on anifrolumab and its potential for the treatment of moderate-to-severe systemic lupus erythematosus: evidence to date</p>

Abstract: Previous reports have described the appearance of systemic lupus erythematosus (SLE) cases following interferon-α (IFN-α) therapy, IFN-regulated gene expression is significantly increased in SLE, and an association between SLE and gene variants belonging to IFN downstream pathways has been shown. Based on this, targeting of IFN and of their signaling pathways has appeared to be interesting developments within the field of SLE therapy. Different specific type I IFN antagonists have been studied in clinical tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 44 publications
0
25
0
3
Order By: Relevance
“…Although the trial did not see a benefit in Based Composite Lupus Assessment (BICLA), the drug did provoke anti-IFN-a2b serum antibodies and decreased the IFN gene signature in 91% of patients. An anti-IFNAR1 monoclonal antibody, anifrolumab, has been evaluated in 11 clinical trials for SLE (9), Sjögren's (1), and rheumatoid arthritis (1), with encouraging results (53). A recent phase III trial in SLE did not meet its primary endpoint of response, as per the SLE Responder Index; however, the same group conducted another phase III trial using the of British Isles Lupus Assessment Group (BILAG)-BICLA response as the primary endpoint and reported a statistically significant higher percentage of patients having a response as well as seeing a decrease in secondary endpoints, suggesting that a chronic IFNa response in SLE patients may contribute to disease pathogenesis (48).…”
Section: Canonical and Non-canonical Signaling In Autoimmune Diseasesmentioning
confidence: 99%
“…Although the trial did not see a benefit in Based Composite Lupus Assessment (BICLA), the drug did provoke anti-IFN-a2b serum antibodies and decreased the IFN gene signature in 91% of patients. An anti-IFNAR1 monoclonal antibody, anifrolumab, has been evaluated in 11 clinical trials for SLE (9), Sjögren's (1), and rheumatoid arthritis (1), with encouraging results (53). A recent phase III trial in SLE did not meet its primary endpoint of response, as per the SLE Responder Index; however, the same group conducted another phase III trial using the of British Isles Lupus Assessment Group (BILAG)-BICLA response as the primary endpoint and reported a statistically significant higher percentage of patients having a response as well as seeing a decrease in secondary endpoints, suggesting that a chronic IFNa response in SLE patients may contribute to disease pathogenesis (48).…”
Section: Canonical and Non-canonical Signaling In Autoimmune Diseasesmentioning
confidence: 99%
“…This observation alone cannot provide information on the presence of interferon in inflamed tissue or the contribution of interferon to tissue pathology such as lupus nephritis. The efficacy of targeting type 1 interferons to treat SLE remains under investigation in large clinical trials 27 . Furthermore, using mouse models to inform therapeutic strategies in SLE has had limited success 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the authors found no differences between skin biopsies of patients with and without systemic involvement. Blocking IFNα receptor improved CLASI scores for SLE patients with cutaneous involvement in a phase II trial [ (152,153), reviewed in (154)]; however IFNγ blockade did not improve CLASI scores in DLE patients (155). Single cell resolution may be necessary to elucidate the precise roles of different IFNs in pathogenesis.…”
Section: Paracrine Signals: Cytokines Hormones and Master Regulatorsmentioning
confidence: 99%